(untitled) (Cultura Económica, 2019)
Is enlightened self-interest a reason to opt for a policy of corporate social responsibility? Is it enough as a moral reason or is it only a strategic reason? The author revises the recent debate prompted by the reports of The Economist about Corporate Social Responsibility and looks for a more suitable reason based on the “social function of the corporation”. Preziosa understands the corporation as a result of collective action and as an institutional agent with moral character.